Probability and statistics - Spiegel, Murray R.; Schiller, John J.; Srinivasan, R. Alu. (New york McGraw hill, 2013)
A study-guide to probability and statistics that includes coverage of course concepts and 897 fully solved problems.
Part I: Probability -- Basic Probability -- Random Variables and Probability Distributions -- Mathematical Expectation -- Special Probability Distributions -- Part II: Statistics -- Sampling Theory -- Estimation Theory -- Tests of Hypotheses and Significance -- Curve Fitting, Regression, and Correlation -- Analysis of Variance -- Nonparametric Tests -- Bayesian Methods.
Includes indexes.
Keywords: Probabilities -- Problems, exercises, etc; Probabilities -- Outlines, syllabi, etc; Mathematical statistics -- Problems, exercises, etc; Mathematical statistics -- Outlines, syllabi, etc